Jornalismo on demand: o consumo da notícia pelo usuário globoplay em Sergipe - Bitencourt, Priscilla Terezinha (2024)
This research aims to investigate the consumption behavior of users of the Globoplay platform in Sergipe. For this understanding, complementary methods of analysis were used, the first being an analysis of the platform's content with the investigation of the ways in which journalistic content is offered. Next, a non-probabilistic survey was conducted, in which 587 respondents answered a questionnaire aimed at users, subscribers and non-subscribers who consume and who declare not to consume journalistic products.In a third stage of this investigation, a Focus Group was carried out with the presence of a heterogeneous group of users identified as subscribers, non-subscribers, consumers and non-consumers of journalism. The results identify patterns of consumption behavior of the platform's users, as well as the impact of journalistic production from the perspective of its users. The range of information obtained in this investigation allows the previous identification of the inherent characteristics of on-demand journalism in Sergipe, as well as its gaps and potential fields of development in terms of formats, content and approaches.